Proposta de estrutura e de método para coordenação da qualidade em cadeias de produção agroalimentares. - Borrás, Miguel Angel Aires (2005)
The questions on food quality and food safety are main problems to elaborate healthy agri-food products from ecological process. Those factors, associated with the increasing agri-food sector s competitiveness are basics to conquest new competitive levels by agri-food supply chains (ASC). It follows that is primordial that ACS achieves the assurance of the quality and safety for its products. This can be obtained with the integrated management of quality in the production stages performed along all chain. On this thesis, the type of management which reaches all ACS is called quality coordination. The thesis proposes a structure (Structure for Quality Coordination SQC) and a method (Method for Quality Coordination MQC) which can help the ACS to coordinate the quality into its segments. Thus, the research is based on wide bibliography revision that discusses theoretical concepts on agri-food chain, supply chain, quality management, agri-food coordination and change theories. This revision generated: a) the quality coordination concept; b) the proposal of the SQC and MQC; and c) the SQC/MCQ Implantation Procedure (SMIP). The SQC is composed of the own ACS with its segments and agents, coordinating agent, quality product and quality management requirements and for the MQC. The MQC is composed of eight modules which claims: a) to identify the Demanded Quality (DQ) and deploy it in product and management requirements; b) to follow and evaluate the quality management practices and ACS performance indicators; and c) to propose and control improvement plans. Besides, the SQC and the MQC was evaluated in workshop accomplished with representatives of alcohol and sugar factories and rural producers. A brief illustration of the SMIP and SQC/MQC using in the Brazilian apple ACS is presented too. On this illustration is discussed the financial and technical viability of the SCQ/MQC. Therefore with a wide theoretical background is possible conclude that the SCQ and MQC can contribute to assure the quality and safety of agri-food products, improving the ACS competitiveness.